1993
DOI: 10.3109/10799899309073680
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Stable Expression and Desensitization of the Human Dopamine D1B / D5 Receptor

Abstract: The sub-family of dopamine D1-like receptors is now known to be comprised of at least two members: the originally cloned D1 receptor (herein referred to as the D1a receptor) and a related receptor referred to as the D1b, D1 beta or D5 dopamine receptor (herein referred to as the D1b/D5 receptor). Here, we characterize the D1b/D5 receptor expressed transiently in COS-7 cells and permanently in Ltk- cells. Transiently expressed human D1b/D5 receptors bind the D1 specific ligand [125I]SCH 23982 saturably and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 14 publications
4
18
0
Order By: Relevance
“…2 Prefrontal Dopamine Electrophysiology and Schizophrenia 167 cellular recordings at 34 Њ C). The short duration application time 30-90 s) implemented in these studies served to minimize rapid D1 receptor desensitization (Jarvie et al 1993;Ng et al 1994Ng et al , 1995 Dumartin et al 1998).…”
Section: Ionic Bases Of Direct Dopamine Actions On Pyramidal Neurons mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Prefrontal Dopamine Electrophysiology and Schizophrenia 167 cellular recordings at 34 Њ C). The short duration application time 30-90 s) implemented in these studies served to minimize rapid D1 receptor desensitization (Jarvie et al 1993;Ng et al 1994Ng et al , 1995 Dumartin et al 1998).…”
Section: Ionic Bases Of Direct Dopamine Actions On Pyramidal Neurons mentioning
confidence: 99%
“…2 Prefrontal Dopamine Electrophysiology and Schizophrenia 167 cellular recordings at 34 Њ C). The short duration application time 30-90 s) implemented in these studies served to minimize rapid D1 receptor desensitization (Jarvie et al 1993;Ng et al 1994Ng et al , 1995 Dumartin et al 1998).More recently, other intracellular and patch-clamp studies also detected an early transient suppression of input resistance that results in a late onset of first spike latency (responses start at ‫ف‬ 2 min after a 5-min long dopamine or D2/3/4 agonist application with the responses lasting for ‫ف‬ 5 min) (Geijo-Barrientos and Pastore 1995; Gulledge and Jaffe 1998). Responses from some of the same cells also show a delayed increase in neuronal excitability, as shown by a rebound earlier onset of first spike latency evoked by the same depolarizing pulse in PFC pyramidal neurons (Gulledge and Jaffe 1998).…”
mentioning
confidence: 99%
“…Later studies revealed that the human D 5 and the rat D 1B receptor sequences are in fact orthologous [Jarvie et al, 1993]. Genes are referred to as 'orthologous' when homologous sequences present in different species originate from a gene already present in their common ancestor.…”
Section: Two Families Of Dopamine Receptors In Mammalsmentioning
confidence: 99%
“…It suggests that one functional differentiating characteristic of the D 1B receptor is its constitutive activity, a property inherent in the mammalian D 5 /D 1B receptor (34,35) and which appears to have been absolutely conserved throughout the evolutionary course of the D 1B receptor subfamily. As such, constitutive activation of adenylate cyclase by the D 1B receptor system appears fundamental to this receptor subtype and functionally relevant to the physiology of dopamine in the vertebrate nervous system.…”
Section: Cloning and Sequencing Of Four Distinct D 1 -Like Receptormentioning
confidence: 99%